Thailand Economic Monitor, November 2010 - World Bank (Washington, DC, 2017)
Growth has slowed down since the second quarter, but exceeded expectations. Considering the 1) political turmoil; 2) robust growth during the rebound; and 3) slowdown in advanced economies, the Thai economy was expected to contract by more than it did in the second and third quarters. The output of the manufacturing sector expanded in the second quarter, led by still-growing exports and robust private consumption. Demand indeed appears to have been higher than production, as some orders had to be filled by drawing down on inventories. However, a sharp contraction in tourism led Gross Domestic product (GDP) overall to contract in the quarter. The FY10 fiscal deficit was much smaller than initially feared when the budget was proposed. The budget for FY10 was prepared at the trough of the global financial crisis in February 2009 and anticipated only 1.35 trillion baht in revenues. Inflation levels have been low and stable but persistent increases in food prices could pose risks. Overall, slower growth in advanced economies will translate into lower GDP growth Thailand for the next two to three years. Notwithstanding a deceleration in the second half because of the waning global inventory cycle, year-on-year growth in 2010 is expected at 7.5 percent due to the low base of 2009 and the strong first half. Quarter-to-quarter growth will pick up modestly in 2011 to average over 4 percent, but the relatively high base in 2010 results in a year-on-year growth rate of 3.2 percent for 2011.